2022
DOI: 10.1038/s41531-022-00288-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modality machine learning predicting Parkinson’s disease

Abstract: Personalized medicine promises individualized disease prediction and treatment. The convergence of machine learning (ML) and available multimodal data is key moving forward. We build upon previous work to deliver multimodal predictions of Parkinson’s disease (PD) risk and systematically develop a model using GenoML, an automated ML package, to make improved multi-omic predictions of PD, validated in an external cohort. We investigated top features, constructed hypothesis-free disease-relevant networks, and inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…7 ). The co-location of genes and eQTLs, identified as being important for Parkinson’s disease diagnosis, 38 within the nine clusters supports the potential importance of the gene–gene interactions and enriched pathways in Parkinson’s disease.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…7 ). The co-location of genes and eQTLs, identified as being important for Parkinson’s disease diagnosis, 38 within the nine clusters supports the potential importance of the gene–gene interactions and enriched pathways in Parkinson’s disease.…”
Section: Resultssupporting
confidence: 53%
“…Makarious et al 38 recently used a multimodal machine learning approach, incorporating multi-omics datasets, to inform and improve predictions of Parkinson’s disease. Beyond the 90 GWAS SNP signals (which collectively were the top genetic feature), they also identified rs10835060 and rs4238361 as two SNPs that impact on Parkinson’s disease biology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent pioneering studies have reported that combining multiple pieces of information, including disease-associated protein levels, the presence of α-synuclein seeds, genomics, transcriptomics, and clinical information, can improve the accuracy of diagnosis and/or stratification. 7579 However, previous studies have rarely succeeded in improving all aspects of diagnosis, motor symptom stratification, and cognitive symptom stratification. 80 It has also been reported that the polygenic susceptibility that drives the onset of PD and the progression of symptoms may not be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Source code and documentation are available at https://genoml.com/ and on GitHub (https://github.com/GenoML/genoml2). The process we used for selecting the best p value threshold mirrored that in Makarious et al 22 We ran the discrete supervised learning workflow for munging, followed by training on a series of p value thresholds taken from Chang et al 18 PD GWAS summary statistics, which included each incremental order of magnitude ranging from 0.01 to 1 × 10 −8 . Each model included SNPs as well as sex, age, and 20 principal components (PCs) to account for population stratification.…”
Section: Methodsmentioning
confidence: 99%